Cosmopolitanism In Dravidian Ideology: A Hybrid Political Framework Beyond Borders - R. Raviraja, R. Raviraja; E. Ravi, E. Ravi (Journal of Neonatal Surgery, 2025)
Dravidian ideology, historically rooted in South India, has evolved as a powerful socio-political movement advocating social justice, regional identity, and linguistic pride. While often perceived as regionalist, Dravidian thought incorporates elements of cosmopolitanism, fostering inclusivity, rationalism, and anti-caste ideals that transcend territorial boundaries. This paper examines the hybrid nature of Dravidian cosmopolitanism, arguing that its ideological framework integrates local identities with global progressive values. By embracing social democracy, secularism, and egalitarianism, Dravidian politics challenges hegemonic nationalism while maintaining a transnational outlook. The study highlights the movement’s engagement with global discourses on human rights, social equity, and cultural exchange, illustrating its relevance beyond South India. It also explores how Dravidian parties and intellectuals navigate the balance between regional assertion and universalist ideals, creating a political model that defies traditional binaries of nationalism and globalization